Aspergillus fumigatus induction of IL‐33 expression in chronic rhinosinusitis is PAR2‐dependent. (11th April 2019) - Dietz, Caroline J.; Sun, Hua; Yao, William C.; Citardi, Martin J.; Corry, David B.; Luong, Amber U.
Abstract : Objective: In the pathophysiology of chronic rhinosinusitis with nasal polyps (CRSwNP), Aspergillus fumigatus (A. fumigatus) can upregulate IL‐33 from human sinonasal epithelial cells (SNECs), which then activates innate lymphoid cells causing release of IL‐13, an important driver of allergic inflammation. However, the mechanism by which A. fumigatus mediates the induction of IL‐33 expression remains to be elucidated. The objectives of this study were to determine the specific fungal component(s) and the receptor responsible for mediating the A. fumigatus induced increase in IL‐33 expression in SNECs from patients with CRSwNP. Methods: SNECs from CRSwNP patients were cultured and stimulated with various fungal components in the absence or presence of 4‐(2‐Aminoethyl)benzenesulfonyl fluoride hydrochloride, an irreversible serine protease inhibitor, or GB83, a reversible protease activated receptor 2 (PAR2) inhibitor. IL‐33 expression was evaluated using quantitative real‐time polymerase chain reaction (qRT‐PCR). PAR2 expression was examined in inflamed mucosa from nonatopic control and CRSwNP patients. Results: Elevation of IL‐33 expression in primary SNECs was found in response to fungal protease but not fungal cell wall components. PAR2 expression was elevated in inflamed mucosa from CRSwNP patients in comparison to controls. The A. fumigatus fungal protease‐mediated elevation in IL‐33 expression by human SNECs was serine protease‐ and PAR2‐dependent. Conclusion: These data suggest that serine protease activity of A. fumigatus is capable of inducing IL‐33 expression in CRSwNP SNECs via PAR2, a potential therapeutic target in the treatment of CRSwNP. Level of Evidence: NA Laryngoscope, 129:2230–2235, 2019